a^2 - b^2 = (a + b)(a - b)
In this case
49x^4y^2 - 4z^2
= (7x^2y)^2 - (2z)^2
= (7x^2y + 2z)(7x^2y - 2z)
Factors are (7x^2y + 2z) and (7x^2y - 2z)
Answer:
D) 7x^2y + 2z
Answer:
see explanation
Step-by-step explanation:
Under a translation < 5, - 9 >
5 is added to the original x- coordinate and 9 is subtracted from the original y- coordinate, that is
A(1, 4 ) → A'(1 + 5, 4 - 9 ) → A'(6, - 5 )
B(2, - 2 ) → B'(2 + 5, - 2 - 9 ) → B'(7, - 11 )
C(- 3, 2 ) → C'(- 3 + 5, 2 - 9 ) → C'(2, - 7 )
Answer:
can u show me a picture of this problem.
Step-by-step explanation:
Answer:
Step-by-step explanation:
Slope is 0
Answer:
Step-by-step explanation:
A